Des cocottes en papier - Danièle Alexandre-Bidon (Revue d'ethnoécologie)
Much present in comics (some 1 500 strips of which 30 % have a gallinaceous hero), rural icon, the hen is very often anthropomorphised.Sometimes it stands for maternal values (protective and wise), sometimes it is depicted as stupid and constitutes a source of jokes. The rooster's image, and that of the hen also, is used as a political metaphor as soon as the beginning of the XXth century. If the rooster is on the conquerors side, chickens and hens are in the oppressed camp. When dealing with poultry breeding, comics books are reflecting social and economics issues of their times. Since the end of the 1970's in the US and the end of the 2000's in France the theme is an opportunity to denounce industrial food, fast food and junk food.